Agro-Morphological Diversity (Qualitative Traits) of Oryza sativa L. Cultivated in Paiyunpata Village, Baglung, Nepal - Pathak, Hom Nath (Nepal Journal of Science and Technology, 2020)
The study was carried out in Paiyunpata, Baglung-13, which lies in the southern part of Baglung Bazaar, Central Nepal. The main objective of the present study was to study the agro-morphological traits of rice varieties cultivated in the study area and make easy ways for germplasm conservation. Direct observation and measurements were carried out to collect primary data.Agro-morphological characters of 19 landraces of rice in the study sites were measured in terms of qualitative characters and made ways easy for germplasm conservation. Besides, the varied landraces may be suggested to breeding for crop improvement, but patents should be that of the community.